Assessment of Probiotic Properties of Lactic Acid Bacteria from Traditional Sourdoughs for Bread-Making in Turkey against Some Gut Conditions - Murat Doğan; İsmail Hakkı Tekiner (Journal of Applied Food Technology, 2019)
This study aims to assess the probiotic properties of Lactic Acid Bacteria isolated from the traditional sourdoughs used for bread making in Turkey against some gut conditions. A total number of 29 samples from twelve provinces of Turkey were collected, and screened for the presence of lactic acid bacteria using microbiological methods. The microbiological screening yielded 148 presumptive isolates. Of them, 62.8% were characterized as lactic acid strains by VITEK® MS. Following that, the characterized isolates were subjected to probiotic property testing, including gastric acid resistance, bile resistance and hydrophobic ability. The results showed that 44.1% exceeded gastric pH resistance, 33.3% survived under gastrointestinal system bile salt conditions, and 10.8% exhibited high hydrophobicity ability. In conclusion, our study revealed that only 4.3% (1 Enterococcus faecium, 1 Lactobacillus brevis, 1 Lactobacillus pentosus, and 1 Lactobacillus plantarum) out of 93 lactic acid bacteria isolated from the traditional sourdoughs could meet all probiotic requirements against some gut conditions.